POINT-SOURCE ELECTROMAGNETIC EXCITATION OF A LAYERED SPHERE - TSITSAS, N. L.; ATHANASIADIS, C. (Mathematical Methods In Scattering Theory And Biomedical Engineering, 2006)
A layered sphere is excited by a point-source, generating spherical electromagnetic waves. The point-source is located either in the interior or in the exterior of the layered sphere. The solution of the corresponding boundary value problem, which is obtained by applying a combination of Sommerfeld's and T-matrix methods, yields exact expressions of the fields in every layer and in the exterior of the layered sphere. A recursive algorithm with respect to the number of layers is extracted for the computation of the fields in every layer. The results corresponding to a point-source located in the exterior of the sphere recover known results for spherical wave scattering by a layered sphere.